Sub-Hepatic Appendicitis: Case Report - ALHOSENI, MASHAL; Alhusaini, Yousef; Alenezi, Jarah; Almutairi , Nora (International Journal of Innovative Research in Medical Science, 2023)
Introduction and importance: Subhepatic appendicitis, a rare variant of acute appendicitis, presents unique challenges in diagnosis and management. This discussion will delve into its incidence, diagnostic approach, and prognosis. Case presentation: A 58-year-old female patient with multiple co-morbidities presented with 2 days of right-sided abdominal pain fever and vomiting. CT scan was done showing features of sub-hepatic appendicitis. A Laparoscopic appendectomy was done. Clinical discussion: Subhepatic appendicitis is considered an uncommon manifestation of acute appendicitis. Due to its unusual anatomical location, it can pose difficulties in recognizing and diagnosing, mimicking other conditions. The prognosis of subhepatic appendicitis depends on early detection and intervention. Delayed diagnosis could lead to complications. Conclusion: Subhepatic appendicitis, a rare condition, poses distinct clinical challenges. The report analyzes its prevalence, symptoms, diagnosis, and treatment, aiming to enhance comprehension of its impact on medical and surgical approaches.